(untitled) (Discussion Papers, 2012)
This study examines capacities for “regionbuilding” on Hungary’s eastern borders in anticipation of the next round of EU enlargement and the inauguration of the EU’s New Neighbourhood Policy. This includes, among others, co-operative structures, governance practices, conflict minimising dialogue and strategies for joint economic development. For several years now, the Centre for Regional Studies of the Hungarian Academy of Sciences has been carefully scrutinising potentials for border transcending co-operation practices and urban networks between Hungary, Romania and the Ukraine. The Hungarian-Romanian and the Hungarian-Ukrainian border sections and border regions touch Hungary from the east. Although they share several common characteristics, still it is reasonable to survey them separately. Both eastern border sections of Hungary were designated by the Peace Treaty of Trianon concluding World War I; however, there are significant differences between them both as regards their past to date and their future prospects. In the case of the Hungarian-Romanian border section, on both sides of the border the same state has existed since the borders were drawn, while several different state formations succeeded each other on the Ukrainian side of the present Hungarian-Ukrainian border. Another significant difference is the fact that this border section is the only gate of Romania to the West, whereas the Ukraine can join the European socio-economic and cultural affairs via Slovakia and Poland, as well. In addition, the public administrative and the statistical system of Romania and The Ukraine are considerably different from both one another and the Hungarian system. We can see fundamentally different historical, socio-economic and political dimensions, also different traditions and ways of life in Romania and The Ukraine. The region’s socio-economic development is significantly lagging behind the European Union’s average indicators. The total Hungarian-Ukrainian frontier zone and the northern Hungarian-Romanian border are peripheral areas within their mother countries. Thus, two peripheral areas are meeting at the border. Since Hungary’s EU accession the Hungarian-Ukrainian border is a longterm, the Hungarian-Romanian border is a short-term external border of the EU. Before the change of the political system (1989) East-Hungarian borders were very strict. The East Central-European political transformation opened them up but the quality and intensity of cross-border cooperation is still low, very few economic cooperation projects have been established so far. The enhancement of cooperation activities is further hindered by ethnic problems. For this reason the current researches are seeking for further areas of CBC.